MODEL PENANGANAN PENGARUH KERUSAKAN JALAN NASIONAL DI PROVINSI LAMPUNG (Studi kasus Jalan Soekarno Hatta Ruas Bakauheni – Tugu Radin Intan Provinsi Lampung) - Tosulpa, M. Enriko; Putranto, Leksmono S; Sulistyorini, Rahayu (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2025)
The Lampung Province holds a strategic position as a connecting route between Sumatra and Java, serving as a land logistics gateway between the islands. The national roads in this province play a crucial role in supporting economic efficiency by reducing time and distribution costs. However, the poor condition of road infrastructure—triggered by low pavement quality and excessive loading hinders trade and transportation activities and worsens interregional integration. This study aims to identify and analyze the main parameters causing road damage and to establish priorities for handling national roads in Lampung Province. Data were obtained through interviews, questionnaires, and documentation from relevant stakeholders. The method used is the Analytic Hierarchy Process (AHP). The analysis results indicate six main parameters causing road damage: International Roughness Index (IRI), Pavement Condition Index (PCI), drainage effectiveness, Remaining Service Life (RSL), Average Daily Traffic (LHR), and Vehicle Damage Factor (VDF). Based on AHP weighting, IRI received the highest weight (27%) and is identified as the primary indicator of road damage. The top priority for road maintenance is the Bts Sukamaju – Km 10 Panjang Bandar Lampung section, which stretches for 5 kilometers.